Targeting CFTR: How to Treat Cystic Fibrosis by CFTR-Repairing Therapies - D. Amaral, Margarida (Current Drug Targets, 2011)
Several novel compounds recently appeared as promising leads to develop effective drugs against the basic defect in Cystic fibrosis (CF) and the first rationale therapies for CF relying on the understanding of the basic defect started to hit the clinical setting. Most of these efforts are focused on correcting the F508del mutation (occurring in ∼90% of CF patients) which causes misfolding of the CF transmembrane conductance regulator (CFTR) protein, the intracellular retention of such abnormal conformation by the endoplasmic reticulum quality control and premature degradation, thus precluding CFTR from reaching the cell membrane where it normally functions as a cAMP-stimulated Cl- channel. Here, several rationale therapeutic strategies are briefly reviewed, namely, mutation-specific (or “CFTR-repairing”) approaches (with a particular focus on the cellular defect associated with F508del-CFTR), manipulation of other ionic (non-CFTR) conductances and gene therapy. Still more innovative strategies, such as manipulation of the proteostasis network, displacement of molecular chaperones, targeting mutant CFTR by in silico small-molecule screens and systems biology approaches are also discussed.
Keywords: ionic conductances